The Integrated Component-Based Knowledge Management System (ICB-KMS) for Mental Healthcare - Siti Rohajawati (Jurnal Indonesia Sosial Teknologi, 2024)
The importance of mental health in the world needs special attention. A country with a dense and high population, such as Indonesia, is known to be vulnerable to the prevalence of mental disorders due to the pressure of various factors such as work, social, cultural, and environment. The high number of mental disorders threatens the country's economy because they are not optimally productive. Currently, accurate mental health data is complex due to stigma and a lack of understanding and knowledge in society. This research aims to apply the integrated component-based knowledge management system (ICB-KMS) framework for mental health. The study was conducted in five mental hospitals in the A category using quantitative and qualitative methods. More than 200 pieces of data were collected from practitioners and healthcare professionals (doctors and psychiatrists), medical staff, nurses, management, stakeholders, and policymakers. Four of the seven phases of the ICB-KMS framework were successfully carried out, i.e., requirement analysis, system design and architecture, knowledge acquisition and integration, and user interface design interaction. The result is a blueprint of ICB-KMS with functional and non-functional systems and application architecture.